Author Correction: 18F-THK5351 PET imaging in patients with progressive supranuclear palsy: associations with core domains and diagnostic certainty - Jung-Lung Hsu (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.